Alternativas biotecnológicas para el control de la pudrición de la corona (Colletotrichum musae) en el Banano (Musa x paradisiaca) - Vecilla Barrera, Pedro Alexander (2025)
In the development of the research based on the "Biotechnological alternatives for the control of crown rot (Colletotrichum musae) in Banana (Musa x paradisiaca)." In which it was raised as objective, to describe the biotechnological alternatives for the control of crown rot (C. musae) in Banana (M. paradisiaca). The methodology, it was determined that the study was carried out in a descriptive type, with a qualitative investigative design, within the development topics were taken such as the botanical characteristics of the Banana, the main phytosanitary problems in the cultivation of banana, crown rot, its description of the disease, main biotechnological alternatives used in the control of crown rot, and finally the mechanisms of action of biotechnological agents for the control of crown production. Regarding the results, several biotechnological options applied in the regulation of crown rot in banana crops and its colonizing effect on the fruit surface were recognized, limiting the access of pathogens to the resources necessary for their development, in addition, facilitating the direct elimination of pathogenic cells. Field research has shown that the use of these agents can decrease up to 60-80%. In conclusion, the analysis highlights various promising biotechnological strategies for the regulation of crown rot in crops and that antagonistic microorganisms are distinguished by their efficient competition for nutrients and space, surpassing pathogens in this way to have a crop that fights the disease.